Economic Burden Analysis of Surgical Site Infections in Multispecialty Hospitals: A Cohort Study with Cost-Effectiveness Evaluation - Yadav, Amit Kumar; Kumar, Krishan (Journal of Contemporary Medical Practice, 2025)
Surgical site infections [SSIs] are known to cause substantial illness and costs during the index hospitalizations, little information exists about the impact of infections diagnosed after surgery, which constitute the majority of SSIs. In this study, using patient questionnaire and administrative data base, we assessed the clinical outcomes and resource utilization in 12-week post –operative period associated with SSIs are recognized after discharge.